Predictors of leadership skills of Pennsylvanian youth. Issue 3 (27th May 2018) - Osmane, Sarah; Brennan, Mark
Abstract: This study was designed to understand the factors contributing to the development of youth leaders. A descriptive correlational study was conducted to reach this goal, and a mixed method approach was used. Four Pennsylvania public high schools with agriculture programs were selected to participate in this study. Data from 421 students were collected (86% response rate) to determine the factors contributing to leadership development. This was coupled with 19 key informant interviews with teachers and students. The findings of this research indicate that social support was the most important predictor of leadership skills. This was followed by civic engagement and social interaction variables. Participation in leadership programs was also related to leadership skills. Additionally, gender differences existed in leadership skills, with females showing higher levels.